Protecting an Internet Web File using Java - Taha, Imad; Naef, Asaad (Al Rafidain University College, 2004)
In this paper, we present a proposed method for protecting a file on a website using java language by dealing with the classes of the HTML file. All steps are programmable and we used the features of windows design in protecting files by checking all its attributes, which provide reasonable security. Using this method, we can protect more than one file in the class for many users of different sites. This method differ from other methods by not providing the program code inside the HTML and difficulty of discovering and analyzing the proposed method because it is inside the class. By using the real time technique we can use our method without getting the help of the Internet Service Provider.